Contemporary jewellery as Aamilatun Jameelah: a creative response to the complexities of a South African Islamic-feminist identity - Khan, Mariambibi (Stellenbosch : Stellenbosch University, 2024)
Thesis MA (VA)--Stellenbosch University, 2024.